Kajian Estetika Bentuk Interior Restoran pada Hotel Shangri-La di Surabaya - Salim, Yelly Monalisa (Intra, 2013)
Design of the restaurant in the hotel has a long life to represent the character of the hotel. Considering the atmosphere inside the restaurant which can be induced by social and environmental conditions. Shangri-La, one of the biggest hotels in Surabaya with Timeless Elegance legend that has some characteristics of fusion type restaurant with lounge, buffet, specialty and has a different special character, but still ongoing. Approach to the theory of aesthetic form of Herbert Read which refers to the aesthetic forms with meanings in it and the arrangement of the forms of expression that creates an object that is the interior of the restaurant Hotel Shangri-La. Methods of research used a descriptive approach. Subject matter within the scope and form of aesthetic expression with the physical limitations of spatial design elements, forming spaces, transitional space, a space filler, and decorative ornamentation. The results explain that the restaurant in the Hotel Shangri-La to apply aesthetic values, while the combination of the elements and principles of design in interior restaurant with variations in the composition to form an expression that is familiar expression equation, quiet, comfortable, open, stable, eternal, natural, warm, familial to the same hotel for the expression differences of each destination restaurant on the lobby Lounge is kemegahaan; celebration, cleanliness in restaurant Jamoo; Chinese culture at Shang Palace Restaurant and the creation of a variety of room ambience.